The functional mechanisms of phosphite and its applications in crop plants - Li, Zhenyi; Kong, Xiangjiu; Zhang, Zhiqiang; Tang, Fang; Wang, Mingjiu; Zhao, Yan; Shi, Fengling (Frontiers in Plant Science, 2025)
Phosphite (Phi), the reduced form of phosphate (Pi), is characterized by its stability, high solubility, efficient transport, resistance to fixation in soil, and widespread occurrence in natural environments. Although Phi exhibits greater suitability than Pi as a soil fertilizer, it cannot be metabolized by plants. In agricultural applications, Phi serves as a bio-stimulant, fungicide, herbicide, and has other purposes. As a bio-stimulant, Phi has been shown to promote plant growth, enhance stress resistance, and improve fruit quality. Additionally, when used as a fungicide or pesticide, it effectively inhibits the growth of phytopathogens in various crop species. The discovery of the phosphite dehydrogenase (ptxD) gene in microorganisms has significantly expanded the potential applications of Phi, including its use as a herbicide, phosphatic fertilizer, and a selectable chemical for generating marker-free transgenic plants. Therefore, the dual fertilization and weed control system of ptxD/Phi facilitates the utilization of Phi as the sole phosphorus source while concurrently suppressing the evolution of herbicide-resistant weeds in the future. Notably, ptxD also acts as an ideal selectable marker because its resistant is specific to Phi, thereby eliminating the risk of false positive clones. The application of Phi provides a promising strategy for addressing phosphorus resource shortages and improving the efficiency of phosphatic fertilizers in agriculture. Furthermore, Phi is considered an environmentally friendly fertilizer, as it contributes to the mitigation of eutrophication. In prospect, Phi is anticipated to play a significant role as a chemical fertilizer that promotes the sustainable development of agriculture. In this review, we provide a comprehensive analysis of the functional mechanisms of Phi and its current applications in agriculture, with the aim of offering deeper insights into its potential benefits and practical utility.